Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ribaf.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in the Vietnamese banking system: A DEA double bootstrap approach

Abstract: This study analyses bank efficiency in Vietnam from 1999 to 2009. We use a unique data sample that allows us to capture the development of the Vietnamese banking sector over the last decade. We apply an advanced methodological approach introduced by Simar and Wilson (2007) to examine bank efficiency in Vietnam. An integral part of the analysis is to explore the determinants of bank efficiency. The results indicate that large and very large banks are more efficient than small and medium sized banks with small b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 21 publications
6
87
3
1
Order By: Relevance
“…In particular, Stewart et al (2016) revealed that, in Vietnam, small and medium-sized banks were less efficient than large and very large banks, and the small banks had the lowest efficiency ratings. This was supported by Ngo and Tripe (2017) and Nguyen et al (2016) where they both found that SOCBs (which are large in size) were more (cost)-efficient than JSCBs (which are generally smaller).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Stewart et al (2016) revealed that, in Vietnam, small and medium-sized banks were less efficient than large and very large banks, and the small banks had the lowest efficiency ratings. This was supported by Ngo and Tripe (2017) and Nguyen et al (2016) where they both found that SOCBs (which are large in size) were more (cost)-efficient than JSCBs (which are generally smaller).…”
Section: Methodsmentioning
confidence: 99%
“…The development of the Vietnamese banking industry and its performance has been examined by many studies, including market reports from international financial institutions (e.g., WB or IMF) as well as individual researchers (Ngo 2012;Ngo and Tripe 2017;Nguyen and Simioni 2015;Nguyen et al 2016;Stewart et al 2016). In particular, Stewart et al (2016) revealed that, in Vietnam, small and medium-sized banks were less efficient than large and very large banks, and the small banks had the lowest efficiency ratings. This was supported by Ngo and Tripe (2017) and Nguyen et al (2016) where they both found that SOCBs (which are large in size) were more (cost)-efficient than JSCBs (which are generally smaller).…”
Section: The Vietnamese Banking System and Its Efficiencymentioning
confidence: 99%
“…23 The SBV targeted 6 to 7 mergers and acquisitions in the banking sector in 2014, and a 50% reduction in the number of commercial banks in the period of -2017(WB, 2014. As large and very large banks are more efficient than small and medium-sized banks (Stewart et al, 2016), the SBV had encouraged big banks such as Bank for Foreign Trade of Vietnam, Bank for Investment and Development of Vietnam or Vietnam Bank for Industry and Trade to merge with smaller banks. This is not only to increase their size and promote economies of scale it is also to "support" each other in development.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the SBV should have policies to enhance the development of non-state owned commercial banks (also see Stewart et al, 2016). The recent restructuring plan allows the SBV to intervene in weak credit institutions, leading to the quick and thorough handling of these credit institutions.…”
Section: Resultsmentioning
confidence: 99%
“…The bootstrapping method has recently been used in bank efficiency measurement with DEA (Hou et al, 2014;Stewart, Matousek, & Nguyen, 2016;Moradi-Motlagh & Saleh, 2014;N. Zelenyuk, V. Zelenyuk, 2014;Alhassan & Tetteh, 2017), but the bootstrap was applied to the DEA efficiency scores (Le, Harvie, & Arjomandi, 2017).…”
Section: Methodsmentioning
confidence: 99%